Experiências de estudantes na construção do conhecimento de derivada em aulas de cálculo 1 - Junqueira, Sonia Maria da Silva (2014)
Aiming to point the possibilities of students experiences in Calculus 1 classes, specifically regarding the derivative content, the theoretical choices were conducted around the dialogic relationship of Buber, the inter-human relationship, and also from the choices that lead the human life according Bauman e May and the dimension of the experience of Larrosa, the field of subjectivity in which the problematic Calculus 1 lies. A qualitative with quantitative data survey was delineated having interpretative and descriptive aspects through which a content analysis was planned Bardin and carried out with 186 students majoring engineering, mathematics, physics and chemistry enrolled in a Public Federal University. The data collection was done through three different approaches, the first and the second revealed subjective hypothesis identified from the investigated subjects talk, and the third, conducted by representations shown in Initial Concept Maps. It was concluded that the experience in Calculus 1 classes has been of reciprocity, in a two-way action that includes contents and subjects of the experience; of singleness, by the subjectivity and identity of each subject; of unpredictability, by the uncertainties, dangers and possibilities of the experience; of temporality, because it dispenses the recognition of distinct time and space to the subjects of the experience. The investigated subjects showed aspects apparently contradictory that however, denoted complementarities. They showed that students who had a weaker base in mathematics reached as many positive results as the negative ones, and that personal goals contributed to the adaptation and development in the school subject, showing aspects of co-responsibilities although they were not the same among the subjects, revealing marks of a process particular in choices as well. Yet, it was highlighted that the strengthening of the transparency mechanism and institutional communication could contribute to the process of development of those subjects. Facing Calculus 1, the students showed emotions, feelings. Facing the derivative they were incipient. However, they revealed marks of experiences that consolidate themselves in the construction of knowledge